Pengamatan Keanekaragaman Jenis Ikan Genus Canna Daerah Kecamatan Medan Tembung Kabupaten Deli Sesrdang - Dita Khairanti; Zahwa Adiesty; Mira Wahyuni Nasution; Miftahuddin Miftahuddin (Departement of Mathematics Education, 2023)
Channa fish is a predatory fish species that lives in fresh water and is a type of fish that is popular with the public to serve as food and ornamental fish for pets. There are several types of fish that are not so difficult to find, so they are often used as food by the community, besides that there are also types of channa fish that are used as pets because they have attractive patterns and colors to be used as decorations. Channa fish are not difficult to reproduce, it is enough to pay attention to food and hormone administration. Apart from that, the benefits obtained are also quite large depending on the type of fish you want to cultivate.